2018
DOI: 10.1016/j.jaut.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity of Treg cells from patients with PBC to low dose IL-12 drives their differentiation into IFN-γ secreting cells

Abstract: IL-12 is a pro-inflammatory cytokine that induces the production of interferon-γ (IFNγ) and favours the differentiation of T helper 1 (Th1) cells. In the presence of IL-12 human Treg cells acquire a Th1-like phenotype with reduced suppressive activity in vitro. Primary biliary cholangitis (PBC) is an autoimmune cholestatic liver disease characterised by high Th1 and Th17 infiltrating cells, reduced frequencies of Treg cells, and a genetic association with IL-12 signalling. Herein, we sought to evaluate the IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 43 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…162 Liaskou et al recently showed that Treg cells from patients with PBC respond to low-dose IL-12 stimulation by significant upregulation of IFN-γ; this effect was mediated by the rapid and strong phosphorylation of STAT4 on Treg cells from patients with PBC providing ongoing support for the importance of the IL12-IL-12Rβ2-STAT4 pathway on Treg cells in disease pathogenesis and potentially treatment. 163 Finally, increased frequencies of Th17 lymphocytic infiltrates have been documented in liver sections from PBC patients, and importantly, they are primarily localized around the damaged interlobular bile ducts in PBC. Most importantly, Th17 skewing is prominent in advanced PBC patients with intensive secretion of IL-23p19 by inflamed hepatocytes around IL-23R, IL-12Rβ2, and IFN-γ expressing degenerated cholangiocytes.…”
Section: Epigenetics Of Pbcmentioning
confidence: 99%
“…162 Liaskou et al recently showed that Treg cells from patients with PBC respond to low-dose IL-12 stimulation by significant upregulation of IFN-γ; this effect was mediated by the rapid and strong phosphorylation of STAT4 on Treg cells from patients with PBC providing ongoing support for the importance of the IL12-IL-12Rβ2-STAT4 pathway on Treg cells in disease pathogenesis and potentially treatment. 163 Finally, increased frequencies of Th17 lymphocytic infiltrates have been documented in liver sections from PBC patients, and importantly, they are primarily localized around the damaged interlobular bile ducts in PBC. Most importantly, Th17 skewing is prominent in advanced PBC patients with intensive secretion of IL-23p19 by inflamed hepatocytes around IL-23R, IL-12Rβ2, and IFN-γ expressing degenerated cholangiocytes.…”
Section: Epigenetics Of Pbcmentioning
confidence: 99%
“…We specifically focused on S100A proteins that have been reported to be increased in saliva and serum of pSS [32] and associated also to a high risk of vascular complications in pSS patients [33–35]. S100 A proteins converged on IL-12 signaling at the GO analysis, a biological process that has been demonstrated to play active roles in the expansion and organization of infiltrative injuries in SS, mirroring specifically DC involvement and Th1 cells differentiation in the disease pathogenesis [6, 36]. We found that S100A proteins were expressed abundantly in saliva, at local sites of inflammation, and we also observed their increase in a stage-manner from pSS-phenotype with normal flow to pSS-phenotype with low flow.…”
Section: Discussionmentioning
confidence: 99%
“…Liaskou et al have previously shown that T reg cells from patients with PBC were highly sensitive to IL-12, but in that study IL-12 concentrations of 10 ng/ml were used (44). This is 2,000 times the concentration we used to demonstrate upregulation of CXCR6 and CD49a on NK cells from PBC patients.…”
Section: Discussionmentioning
confidence: 99%